Analysis and Field Studies of Saltwater Intrusion in a Coastal Aquifer: A Case of Bachok, Kelantan - Hassan, Ruslan (2001)
This dissertation deals with the extent of saltwater/chloride distribution in a two-layered coastal aquifer. The area chosen for the study is located in the Mukim of Bachok, Kelantan which covers an area of 72 km2 about 20 km South East of Kota Bharu. The area mainly consists of a large flat plain, with soils belonging to the Bris complex (82 - 99% sand) and drained mainly by the meandering Kemasin River and its tributaries. Groundwater contamination by chloride has become a threat to this area, economically and to health. Chloride concentrations have exceeded their permissible limits thereby limiting their eventual uses in tobacco farming and as drinking water. The objectives of this study are therefore to analyse the saltwater intrusion and contamination in the area; to obtain the necessary understanding of the chloride movement and distribution; and finally, to ascertain and make reasonable predictions as to the future contamination of the area by the saltwater. The approach taken was two-folds, namely to investigate the chloride distribution in the upper aquifer which is mainly utilized for tobacco farming and to analyse the saltwater intrusion using sharp interface and dispersive approaches in the lower aquifer. The analysis on the extent of chloride distribution in the upper aquifer was based on the field investigation covering a period between 1991 - 1995. The field studies were carried out by comprehensive data collection on the upper aquifer for a period of four (4) years which preceded the one (1) year MARDI study. Field studies on the lower aquifer were carried out for a period of two (2) years (1994 and 1995). The analysis on the Bachok coastal aquifer groundwater systems was done by means of the Regional Groundwater model. The middle stretch of the Kampong Cap transect (DDMl -5) was studied further using the data obtained from Pfeiffer study and the two-zone model. The latter model made use of the discrete space-discrete time approach. To understand the flow paths within the aquifer, an analogue model and PSpice were used. The parameters thus determined were incorporated in the Regional Groundwater model. Chloride distribution for the upper aquifer was then analysed. As for the upper aquifer, there was an increase in the content of chloride concentration compared to the earlier MARDI study despite the seasonal flushing of the saline water. The chloride increased with higher precipitation (November and December annually) in the flood plains, which was opposite to the long held theory that dilution would decrease the concentration.